2019
DOI: 10.1016/j.sdentj.2018.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and characterization of coating pure titanium dental implant with sintered β-TCP by using Nd:YAG laser

Abstract: ObjectivesThis work presents laser coating of grade 1 pure titanium (Ti) dental implant surface with sintered biological apatite beta-tricalcium phosphate (β-TCP), which has a chemical composition close to bone.Materials and methodsPulsed Nd:YAG laser of single pulse capability up to 70 J/10 ms and pulse peak power of 8 kW was used to implement the task. Laser pulse peak power, pulse duration, repetition rate and scanning speed were modulated to achieve the most homogenous, cohesive and highly adherent coat la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…Laser structuring of the titanium not cause any changes in the phases of the Ti as seen in the XRD pattern which is an important thing when dealing with the Ti. But the intensity in this study seen some changes in the intensity of the Ti peak after laser structuring this was due to the strain that induced on the titanium surface after processing our result is confirmed with the results of Safi et al 2019 and Choi et al (21,22)…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Laser structuring of the titanium not cause any changes in the phases of the Ti as seen in the XRD pattern which is an important thing when dealing with the Ti. But the intensity in this study seen some changes in the intensity of the Ti peak after laser structuring this was due to the strain that induced on the titanium surface after processing our result is confirmed with the results of Safi et al 2019 and Choi et al (21,22)…”
Section: Resultssupporting
confidence: 89%
“…XRD pattern of the control only showed the peaks of titanium. While the XRD pattern of the disk sample that treated with the laser for the two designs at the 3 tested laser scans show the present of the TiO 2 beside the Ti this due to the titanium air interaction during the surface structuring 21 ,also results show that at the laser scans 25 seen two peak of TiO 2 for the two design while the laser scans 5 and 15 seen just one peak of TiO 2 with more intensity at 15 laser scans than at 5 laser scans this is due to the increasing in the chance of oxide interaction with the titanium with the increasing in the numbers of laser scans. Laser structuring of the titanium not cause any changes in the phases of the Ti as seen in the XRD pattern which is an important thing when dealing with the Ti.…”
Section: Resultsmentioning
confidence: 96%
“…The 3D artificial construct (cylindrical scaffold and seeded cells) has potential clinical applications in the covering of dental implants and production of biohybrid implants. Further vivo studies could aim to cover dental implants (titanium or zirconia) with sintered β-TCP 40 , 41 in order to simulate natural periodontal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The bioactivity of unmodified Ti surfaces is not sufficient to provide immediate osseointegration, which is essential for ensuring initial stability and long-term durability of implants. 3 Since the surface properties of an implant can impact its biological response, various surface modification strategies have been employed on Ti surfaces including 4 plasma spraying, 5 Nd-YAG laser cladding, 6 micro-arc oxidation, 7 and the deposition of surface oxide layers. 8 Previous studies have shown that porous structures on implant surfaces can enhance implant-tissue integration by providing a surface topography with more defined, reproducible and reliable roughness.…”
Section: Introductionmentioning
confidence: 99%